A map-based web search interface using point of interest aggregation - Jung, K.; Ahn, S.; Ko, H. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2014)
With advent of a mobile computing, the pattern of information search has been changed. Search queries through mobile devices increase; 30% of Google's organic search queries come from mobile devices, and local search, which seeks information with geospatial constraints, also increases. As of 2013 local search on mobile phones continues to grow up to 60% since 2010. However, a large number of web documents cannot be exposed to local search even though they refer to a point of interest (POI) just because they are not explicitly geo-tagged. We are interested in connecting typical web documents to spatial search based on POIs by geotagging web documents. In this paper, we present a map-based web search system that serves geospatial search queries for non-geotagged documents. The proposed system provides with fine-grained local search for typical web pages mentioning several POIs and supports semantic search in accordance with their spatial relation of inclusion. ？ 2014 Springer International Publishing.